Love and Justice: The Foundations of Gudina Tumsa’s Social Engagement and Leadership - Ezekiel Gabissa (Ethiopian Journal of the Social Sciences and Humanities, 2014)
Cultural discourse in Ethiopia appears to retain mixed attitudes about life in the latter years. There is on the one hand, a portrayal of the elderly as socially valued, privileged, respected, and supported. On the other hand, there is a conception that links aging and retirement with sickness, inability, helplessness, and dependency (“ke areju aiyebeju”) and going down the hill. However, academic discourse is only emerging and there is a lot more to be done to uncover what it really feels like to be an elderly in Ethiopia. One such major concern pertains to the very general experiences of life of the elderly and associated factors. The purpose of this study was then to specifically assess the subjective quality of life and perceived adequacy of social support and the possible socio-demographic factors making differences in quality of life. Data were collected through questionnaire administered to a sample of 360 elderly (aged 60 and over) in Arbaminch Town. Data analysis was made through descriptive statistics, one-samplemean test, bivariate correlation analysis, multiple regression, and the forward stepwise variant of multiple regression analysis. Findings indicated that very few elderly had a high quality of life, but the majority had either low or moderate quality of life. Perceived adequacy of social support also took the same pattern contrary to the expectation that the elderly in “developing nations” are believed to enjoy extended social support. Attempts to explain this profile of the elderly yielded that perceived social support and income were indeed the strongest predictors generally explaining about fifty percent of the variance in self-ratings of subjective quality of life. Hence, it was suggested that there is a need to explore other potent factors that would do the remaining fifty percent of the explaining. Other recommendations were also suggested to better address the problem in the future.